Sistem Informasi Notifikasi Pembayaran Perkara Tilang Menggunakan Sms Gateway Berbasis Web - Shella Putri Maqvirah (Journal of Tourism Sciences, Technology and Industry, 2025)
Traffic violation enforcement carried out by traffic officers is implemented in accordance with applicable regulations. Traffic violators are subject to sanctions in the form of warnings or traffic fines, which can be paid at the Lhokseumawe District Attorney’s Office or through Bank Aceh Syariah. However, the management of traffic fine payment data is still conducted manually, causing delays in data processing and monthly as well as annual report preparation due to the absence of an integrated information system. This study aims to develop a web-based traffic fine payment information system that supports data management and notification services. The research method used is a system development approach consisting of data collection, system analysis, system design, implementation, and system testing. The developed system is integrated with an SMS Gateway to deliver payment notifications to traffic violators and is capable of automatically generating monthly and annual traffic fine reports. The results of this study indicate that the proposed system improves the efficiency and accuracy of traffic fine data processing, reduces reporting delays, and facilitates the performance of officers in managing traffic fine payments.